PENGARUH SOCIAL MEDIA MARKETING TERHADAP BRAND AWARENESS DAN PURCHASE INTENTION (Studi Kasus : SMK Kesehatan Sanjiwani Gianyar) - Putra, I Dewa Putu Gede Wiyata; Aristana, Made Dona Wahyu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.11.TAHUN 2020, 2020)
This study examined influence of social media marketing on brand awareness and purchase intention. SMK Kesehatan Sanjiwani Gianyar conducts social media marketing through paid promotions on Instagram and Facebook to increase brand awareness and interest of junior high school students to attend SMK Kesehatan Sanjiwani Gianyar. Data of 2017-2019 shows a decrease in the number of students, even though paid promotions have been carried out through Facebook and Instagram. Method in this study was Structural Equation Modeling (SEM) with the PLS Sample in this research was 100 junior high school students in areas Gianyar, Denpasar, Bangli, Klungkung and Badung regencies. Results in this study shows that social media marketing doesn’t have a significant effect on purchase intention. Social media marketing through paid promotions on Instagram and Facebook creates brand awareness. Increase purchase intention the school must convince the public that school has good quality by exploring the excellence and uniqueness of the school.